1980
DOI: 10.1093/jn/110.11.2297
|View full text |Cite
|
Sign up to set email alerts
|

[14C]-Pantothenate Accumulation by Isolated Adipocytes from Adult Rats of Different Ages

Abstract: Accumulation of radiolabeled pantothenate by isolated adult rat adipocytes was studied in an in vitro system. Maximal uptake after 1 hour incubation occurred in media containing 0.03 mM pantothenate, about 100 picograms (pg) per adipocyte and was less than 1 pg per cell. Using such saturation conditions, uptake was energy- and temperature-dependent, with about 50% maximal accumulation occurring after 5-10 minutes incubation. Uptake was decreased by the addition of unlabeled pantothenate, but not other water-so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Bioavailability of food pantothenic acid for man ranges from 40 to 61 YO, with a mean of 50 YO (Tarr et al 1981). Studies in vivo (Reibel et al 1981) and in vitro (Sugarman & Munro, 1980) have identified one mechanism of transmembrane transport. In the adipocyte of rat the transport of 14C-pantothenate is fast, with a high affinity (half saturation at a concentration of M), saturable, specific, and energy and temperature dependent.…”
Section: Release a N D Absorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioavailability of food pantothenic acid for man ranges from 40 to 61 YO, with a mean of 50 YO (Tarr et al 1981). Studies in vivo (Reibel et al 1981) and in vitro (Sugarman & Munro, 1980) have identified one mechanism of transmembrane transport. In the adipocyte of rat the transport of 14C-pantothenate is fast, with a high affinity (half saturation at a concentration of M), saturable, specific, and energy and temperature dependent.…”
Section: Release a N D Absorptionmentioning
confidence: 99%
“…No degradation products of pantothenic acid are known (Sugarman & Munro, 1980); 1-7 mg/d of intact pantothenic acid are excreted in the urine. Mean excretion increased from 2.3 to 3.9 mg/d as intake increased from 5 to 10 mg (Foss, 1981).…”
Section: E X C R E T I O Nmentioning
confidence: 99%